Reduced SERCA activity underlies dysregulation of Ca2+ homeostasis under atmospheric O2 levels. Issue 5 (22nd December 2017) - Keeley, Thomas P.; Siow, Richard C. M.; Jacob, Ron; Mann, Giovanni E.
Abstract : Unregulated increases in cellular Ca 2+ homeostasis are a hallmark of pathophysiological conditions and a key trigger of cell death. Endothelial cells cultured under physiologic O2 conditions (5% O2 ) exhibit a reduced cytosolic Ca 2+ response to stimulation. The mechanism for reduced plateau [Ca 2+ ]i upon stimulation was due to increased sarco/endoplasmic reticulum Ca 2+ ATPase (SERCA)‐mediated reuptake rather than changes in Ca 2+ influx capacity. Agonist‐stimulated phosphorylation of the SERCA regulatory protein phospholamban was increased in cells cultured under 5% O2 . Elevation of cytosolic and mitochondrial [Ca 2+ ] and cell death after prolonged ionomycin treatment, as a model of Ca 2+ overload, were lower when cells were cultured long‐term under 5% compared with 18% O2 . This protection was abolished by cotreatment with the SERCA inhibitor cyclopiazonic acid. Taken together, these results demonstrate that culturing cells under hyperoxic conditions reduces their ability to efficiently regulate [Ca 2+ ]i, resulting in greater sensitivity to cytotoxic stimuli.—Keeley, T. P., Siow, R. C. M., Jacob, R., Mann, G. E. Reduced SERCA activity underlies dysregulation of Ca 2+ homeostasis under atmospheric O2 levels. FASEB J. 32, 2531–2538 (2018). www.fasebj.org